How to reduce the risk of climate change for the sustainability of rural farmers? Based on evidence from Iran - Moslem Savari; Bagher Khaleghi; Abbas Sheheytavi (Environmental and Sustainability Indicators)
The accelerating impacts of climate change (CC) in Iran pose critical threats to the livelihoods of vulnerable populations, particularly rural communities and farmers. Addressing these challenges requires the adoption of effective adaptation and mitigation strategies, which hinge on a thorough understanding of climate change risk perception (CCRP). This study aimed to identify the key determinants influencing CCRP among Iran's rural farming communities, using the Climate Change Risk Perception Model (CCRPM) as its theoretical framework. The research focused on rural households in Shushtar County, Southwest Iran. The findings demonstrated that the CCRPM exhibited exceptional explanatory power in the Iranian context, accounting for 74.2% of the variance in farmers' CCRP—a notably higher figure compared to similar studies conducted elsewhere. Specifically, the model's components—cognitive, experiential, socio-cultural, and socio-demographic factors— have significant effect on the farmers' CCRP. These results provide valuable insights for policymakers, supporting the development of targeted strategies to enhance the resilience and stability of local communities in the face of CC.